The efficacy analysis method of input–output for substations based on LCC theory. (April 2022) - Li, Na; Wang, Xiaoliang; Li, Chengqi; Zhang, Zhenjun; Zhang, Weiwei
Abstract: Along with the deepening of the power system reform, the input and output evaluation and analysis of asset became more and more important. Arounding the goal of comprehensive optimization of safety, efficiency and cost throughout the life cycle of assets, this paper constructed a quantitative evaluation model for asset input–output analysis, and put forward an input–output analysis method combining the boston matrix method and the equivalent analysis method. Actual substations' input cost and output efficiency analysis verified the method feasibility, which could provide decision-making support for optimizing power grid asset management strategies and enhancing asset value operation benefits.